2021
DOI: 10.1177/1357633x20982773
|View full text |Cite
|
Sign up to set email alerts
|

Marginal assessment of the cost and benefits of aphasia treatment: Evidence from community-based telerehabilitation treatment for aphasia

Abstract: Introduction Few studies have reported information related to the cost-effectiveness of traditional face-to-face treatments for aphasia. The emergence and demand for telepractice approaches to aphasia treatment has resulted in an urgent need to understand the costs and cost-benefits of this approach. Methods Eighteen stroke survivors with aphasia completed community-based aphasia telerehabilitation treatment, utilizing the Language-Oriented Treatment (LOT) delivered via Webex videoconferencing program. Margina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…The framework utilized herein provides what the authors feel is an accurate and logical methodology for evaluating this data and associated cost framework. Furthermore, these findings do agree with other treatment valuation studies that show greater improvements and lower costs per unit of aphasia impairment among individuals with the most severe aphasias [12].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The framework utilized herein provides what the authors feel is an accurate and logical methodology for evaluating this data and associated cost framework. Furthermore, these findings do agree with other treatment valuation studies that show greater improvements and lower costs per unit of aphasia impairment among individuals with the most severe aphasias [12].…”
Section: Discussionsupporting
confidence: 91%
“…Although an emerging literature exists related to cost and cost-effectiveness of treatments for aphasia using measures of impairment [8,[10][11][12][13], little is known about the cost and costeffectiveness of improving functional communication in aphasia. As a comparison, our previous work showed that on average a one-point improvement in impairment as measured by the WAB-R AQ costs approximately $200 [12]. In contrast, a one level change in functional communication cost approximately $1100 for improvements in verbal expression or auditory comprehension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some examples include PWA being anxious about this new and strange remote setting of therapy delivery, their difficulties to pay attention to and stay on tasks virtually due to screen fatigue [29,30,31•], technical difficulties they could encounter as navigating a novel platform of presentation of therapy items, and barriers to accessibility to internet and technology [32]. Although the cost-effectiveness [33,34] and usefulness and efficiency of telepractice in chronic PWA have been reported (for example in terms of PWA's improvements in overall impairment levels and functional communication [34,35], enhanced naming performance [36], positive changes in PWA's conversation through training communication partners [37], and PWA's increased engagement in communicative activities and communication-related quality of life [38]), one should not neglect the factors that determine the suitability and candidacy of PWA to receive online intervention. These factors include type and characteristics of the treatment involved; feasibility for PWA to engage in real-time synchronous therapy versus asynchronous self-mediated practice via telerehabilitation; PWA's endurance and tolerance level of high versus low intensity of training; and the unique inherent perceptual, cognitive, and/or psychomotor barriers in PWA secondary to stroke or brain damage [39].…”
Section: Remote Services To Chronic Pwamentioning
confidence: 99%